COMPARATIVE STUDIES OF PHYTOCHEMICAL AND ANTIOXIDANT ACTIVITY OF IN VIVO PLANT AND IN VITRO CALLUS EXTRACT OF CARDIOSPERMUM HALICACABUM L. - R, THANIARASU; M, LOGESHWARI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The present investigation focuses on the use of Cardiospermum halicacabum L. in their phytochemical and biological activities. Methods: In this study, in vivo stem and in vitro callus ethanolic extracts of C. halicacabum were tested for their phytochemical attributes by qualitative method, Fourier transform infrared (FTIR), antioxidant, antibacterial, and bioactive compound properties. The bactericidal activity of the in vivo stem and in vitro callus extract has been evaluated in both Gram+ve and Gram-ve microorganisms using the disk diffusion method. Results: The highest frequency (78%) of well developed, dark green organogenic callus was induced from stem explant on Murashige and Skoog (MS) medium supplemented with 0.7 mg/l 2,4-Dichlorophenoxyacetic acid (2, 4-D) and 0.5 mg/l benzyl adenine (BA). The results of FTIR spectra confirmed the presence of functional groups in wild stem and in vitro callus extract of C. halicacabum with various peaks. The total phenolic content in ethanolic extract of in vivo plant and in vitro callus was 80.46 mg gallic acid equivalent (GAE)/g dry weight and 76.4 mg GAE/g dry weight, respectively. The highest percentage of tannins was measured at 78.03 in wild stem ethanol extracts followed by 75.22 in callus extract. The antioxidant activity of 2,2-diphenyl-2- picrylhydrazyl (DPPH) ethanol extract was found to be 206.54 μg/ml. IC50 values of the stem extracts of C. halicacabum are 306 μg/ml and 286 μg/ml in callus extract, respectively. Antibacterial activity of the ethanol extract was higher for Staphylococcus aureus (S. aureus) with a 17 mm zone of inhibition. Conclusion: The present investigation recommended that the callus ethanolic extract function as a good source of biologically active compounds and natural antioxidants.